Virtual reality – future of diagnosis, medical education and therapy - Gładysz, Konrad; Szpiech, Kamil; Kuś, Adrian; Szypłowska, Małgorzata; Neścior, Małgorzata (Journal of Education, Health and Sport, 2019)
Virtual reality (VR) has found a variety of applications in the biomedical field. It refers to a computer-generated, three-dimensional image of objects, space and even whole events. It is an extremely promising prospect for medicine, both in the training area and as an aid in carrying out certain procedures or diagnostic processes. The number of conducted research and great interest of scientists in this subject indicates that in the future it will be one of the basic tools of medical personnel in diagnostic processes and therapy. It could be also helpful addition to increase education quality of medical students and specialization education. VR increased the safety of surgical training and has significantly improved it, creating completely new possibilities of imaging complex structures during operations and extending the possibilities of already existing imaging examinations. What is important, VR can be successfully adapted for use by specialists from various, often extremely different medical fields. This article describes the use of virtual reality (both VR and AR technologies) in medical training, procedures and diagnostics.